Principal-Component Analysis-Based Measures of PET Data Closely Reflect Neuropathologic Staging Schemes - Blazhenets, Ganna; Frings, Lars; Sörensen, Arnd; Meyer, Philipp T (The Journal of nuclear medicine (1978), 2021)
Voxel-based principal-component analysis allows for an identification of patterns of glucose metabolism and amyloid deposition related to the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD). The present study aimed to validate these AD conversion-related patterns (ADCRPs) against neuropathologic findings. We included patients from the Alzheimer's Disease Neuroimaging Initiative who underwent autopsy and for whom F-FDG PET (30 AD, 6 MCI, 2 cognitively normal) and amyloid-β (Aβ) PET (17 AD, 3 MCI, 2 cognitively normal) were available. Pattern expression scores (PESs) of the F-FDG- and Aβ-ADCRP were compared with Braak tangle stage and Thal amyloid phase, respectively. Mean F-FDG uptake and mean F-AV-45 SUV ratio (SUVr) in regions of hypometabolism and elevated amyloid load typical of AD, respectively, were used as volume-of-interest-based PET measures. The diagnostic performance for identifying none-to-low vs. intermediate-to-high AD neuropathologic change (ADNC) was assessed for all biomarkers. We observed significant associations between PES of F-FDG-ADCRP and Braak stage (ρ > 0.48, < 0.005) and between PES of Aβ-ADCRP and Thal phase (ρ > 0.66, < 0.001). PES of F-FDG-ADCRP, PES of Aβ-ADCRP, and their combination identified intermediate-to-high ADNC with an area under the receiver-operating-characteristic curve (AUC) of 0.80, 0.95, and 0.98 ( = 22), respectively. Mean F-FDG uptake and mean F-AV-45 SUVr in AD-typical regions were also significantly associated with Braak stage (|ρ| > 0.45, < 0.01) and Thal phase (ρ > 0.55, < 0.01), respectively. Volume-of-interest-based PET measures discriminated between ADNC stages with an AUC of 0.79, 0.88, and 0.90 for mean F-FDG uptake, mean F-AV-45 SUVr, and their combination ( = 22), respectively. Contemplating all subjects with available F-FDG PET and neuropathology information ( = 38), PES of F-FDG-ADCRP was a significant predictor of intermediate-to-high ADNC (AUC = 0.72), whereas mean F-FDG uptake was not (AUC = 0.66), although the difference between methods was not significant. PES of F-FDG-ADCRP, a measure of neurodegeneration, shows close correspondence with the extent of tau pathology, as assessed by Braak tangle stage. PES of Aβ-ADCRP is a valid biomarker of underlying amyloid pathology, as demonstrated by its strong correlation with Thal phase. The combination of ADCRPs performed better than F-FDG-ADCRP alone, although there was only negligible improvement compared with Aβ-ADCRP.